Ground motion vulnerability analysis on road geometric based on remote sensing - Kaffa, Niswah Selmi; Sukojo, Bangun Muljo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Based on spatial plans document of South Sumatera in 2005 – 2019, the study area (South Ogan Komering Ulu, South Sumatera) was categorized as middle–high ground motion vulnerability. This analysis was aimed to determine ground motion vulnerable points along the Sukabumi Sub-district, South Ogan Komering Ulu District, South Sumatera to Tigadihaji Damsite road geometric plan based on remote sensing. The contribution of this research is to determine the location on road geometry that needs slope reinforcement as a mitigation effort. The method used in this analysis was the deterministic method based on ground motion parameters issued by Center for Volcanology and Geological Disaster Mitigation (PVMBG) in 2015 stated in the National Disaster Management Agency (BNPB) Indonesian Disaster Risk (RBI) document in 2016. The eight parameters used were the justification of remote sensing–based processing methods. The data used in this analysis were Hydrology and Geology Final Reports issued by PT Virama Karya (Persero) consultant, Landsat 8 Satellite Imagery band 5 6 7, Digital Elevation Model (DEM), and Geographic Information System (GIS) of South Sumatera. Based on the analysis, it was proven that the study area was categorized as middle–high ground motion vulnerability with the points classified having high ground motion were station 1+225, 1+250, 1+325, 1+350, 1+375, 1+425, 1+450, 1+700, 1+750, 1+775, 1+800, 1+950, and 1+975.